2017
DOI: 10.1037/tra0000146
|View full text |Cite
|
Sign up to set email alerts
|

Impulsivity facets’ predictive relations with DSM–5 PTSD symptom clusters.

Abstract: Objective Posttraumatic Stress Disorder (PTSD) has a well-established theoretical and empirical relation with impulsivity. Prior research has not used a multidimensional approach for measuring both PTSD and impulsivity constructs when assessing their relationship. Method The current study assessed the unique relationship of impulsivity facets on PTSD symptom clusters among a non-clinical sample of 412 trauma-exposed adults. Results Linear regression analyses revealed that impulsivity facets best accounted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 15 publications
(27 reference statements)
7
43
0
Order By: Relevance
“…Risky behaviors may reflect a desire to avoid or escape aversive emotional states (Cooper et al, 2000), or an avoidance strategy to limit emotional and cognitive reactions following PTEs (Pat-Horenczyk et al, 2007). Thus, people may engage in risky behaviors to cope with PTSD’s negative affect (negative alternations in cognition and mood symptoms) and AAR symptoms (Contractor et al, 2014; Roley et al, 2017). Further, research indicates a significant relation between risky behaviors and severity of PTSD’s re-experiencing and avoidance symptom clusters (Pat-Horenczyk et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Risky behaviors may reflect a desire to avoid or escape aversive emotional states (Cooper et al, 2000), or an avoidance strategy to limit emotional and cognitive reactions following PTEs (Pat-Horenczyk et al, 2007). Thus, people may engage in risky behaviors to cope with PTSD’s negative affect (negative alternations in cognition and mood symptoms) and AAR symptoms (Contractor et al, 2014; Roley et al, 2017). Further, research indicates a significant relation between risky behaviors and severity of PTSD’s re-experiencing and avoidance symptom clusters (Pat-Horenczyk et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the impulsive pathway perspective comprehensively details the role of several impulsivity facets (negative urgency, lack of perseverance, lack of premeditation, and sensation seeking) underlying problematic smartphone use (reviewed in Billieux, 2012). The tendency to act impulsively when experiencing intense emotional states, termed as negative urgency (Whiteside & Lynam, 2001) is highly related to PTSD subscale severity, and to NACM symptom severity in particular (Contractor, Armour, Forbes, et al, 2016; Roley, Contractor, Weiss, Armour, & Elhai, 2017); and to problematic phone use (Billieux, Van Der Linden, D’Acremont, Ceschi, & Zermatten, 2007; Billieux, Van Der Linden, & Rochat, 2008). In summary, similar to other addictive impulsive behaviors (Marshall-Berenz, Vujanovic, & MacPherson, 2011; O’Hare, Sherrer, Yeamen, & Cutler, 2009; Sacks, Flood, Dennis, Hertzberg, & Beckham, 2008), excessive smartphone use may be a negatively reinforcing coping strategy for people experiencing negative affect related to PTSD severity (i.e., primarily NACM symptom severity).…”
Section: Introductionmentioning
confidence: 99%
“…When paired with impulsivity, childhood sexual abuse, compared to the other four maltreatment types, might be more likely to influence weight status because of the intrusive and intimate nature of the act(s), including the perpetrator’s contact with the child’s body (Williams, 1993). Interestingly, the results of prior research have indicated that compared to non-sexual trauma exposure, experiences of sexual trauma are more strongly associated with alterations in arousal and reactivity symptoms associated with posttraumatic stress disorder (Guina, Nahhas, Kawalec, & Farnsworth, 2016), which has been linked to impulsivity (Roley, Contractor, Weiss, Armour, & Elhai, 2016). There are likely mediators of the association between childhood sexual abuse and BMI that could help account for the association (e.g., disordered eating, emotion dysregulation, low self-esteem, negative body image; Briere & Scott, 2007; Lanius, Bluhm, & Frewen, 2011; Lavender, Gratz, & Anderson, 2012; Wonderlich et al, 2001); however, these variables were not examined in the current study.…”
Section: Discussionmentioning
confidence: 99%